2021
DOI: 10.1016/j.xinn.2021.100099
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic tracing of asymptomatic transmission in a COVID-19 outbreak

Abstract: SARS-CoV-2 has caused over 100 million deaths and continues to spread rapidly around the world. Asymptomatic transmission of SARS-CoV-2 is the Achilles' heel of COVID-19 public health control measures. Phylogenomic data on SARS-CoV-2 could provide more direct information about asymptomatic transmission. In this study, using a novel MINERVA sequencing technology, we traced asymptomatic transmission of COVID-19 patients in Beijing, China. One hundred and seventy-eight close contacts were quarantined, and 14 COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Another important aspect of asymptomatic viral circulation is the critical role that it can play in the emergence of new genetic variants. 26 This link needs to be studied further.…”
Section: Discussionmentioning
confidence: 98%
“…Another important aspect of asymptomatic viral circulation is the critical role that it can play in the emergence of new genetic variants. 26 This link needs to be studied further.…”
Section: Discussionmentioning
confidence: 98%
“…Since the Delta variant had a much higher fatality compared to its predecessor, Alpha, more severe NPIs were advised to accommodate the rise in cases [ 254 ]. Relatedly, Zhang et al [ 255 ] were able to use SARS-CoV-2 genomes recovered via HC and subsequent phylogeny reconstructions to find evidence of transmission and trace the spread of the virus in asymptomatic patients, which is often overlooked in models calculating the reproductive number (R 0 ) but crucial for understanding the spread of the disease [ 256 , 257 ]. Indeed, HC was extensively employed in tracing outbreak patterns during COVID-19 ( Figure 2 ; Table S1 ), enhancing our understanding of the pandemic’s evolutionary dynamics, virulence, and management.…”
Section: Case Study: Sars-cov-2mentioning
confidence: 99%
“…Unprecedented large-scale PCR screening and routine PCR testing in high-risk regions has identified large numbers of patients that had positive viral nucleic Ivyspring International Publisher acid tests but were found to exhibit no concomitant clinical signs nor typical COVID-19 computed tomography (CT) images in their full course of infection [1], which made these cases distinct from symptomatic infections [2,3]. The occurrence of asymptomatic infections in patients who had tested positive for SARS-CoV-2 has varied from study to study [4][5][6][7][8][9][10]. For example, an early study of the SARS-CoV-2 outbreak on the Diamond Princess cruise ship in Japan indicated that 17.9% of the 634 infected passengers were asymptomatic [11].…”
Section: Introductionmentioning
confidence: 99%